BUILDING COMPETITIVE ADVANTAGE THROUGH IMPLEMENTING TOTAL QUALITY MANAGEMENT IN FAST-MOVING CONSUMER GOODS MANUFACTURING COMPANIES IN INDONESIA - Cahya Purnawidya, Yosua; Toto Raharjo, Susilo (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
Business competition today is very tight and unavoidable. One industrial sector that is not immune from business competition is the consumer products industry which produces daily necessities. The consumer products industry has a fast product turnover in the market. This kind of industry is grouped into the Fast-Moving Consumer Goods (FMCG) industry. The research objective is how to build competitive advantage through the implementation of total quality management in fast moving consumer goods manufacturing companies in Indonesia..The samples from this research are managerial personnel with supervisory positions, or managers of manufacturing companies in the FMCG industry in Indonesia. Determining the sample uses nonprobability sampling with purposive sampling criteria where the researcher provides limits for the sample (Sugiyono, 2016).The minimum sample is 5-10 times the number of indicators, this research uses 23 indicators (23 indicators x 7 = 161 samples).The analysis tool uses AMOS 22.00 Structural method Equations Modelling. Research findings show that there is a significant positive influence of TQM implementation with dimensions of focus on leadership, strategic planning, and customer focus on product quality with a p-value marked *** approaching zero < 0.05 (H1 is accepted). There is.influence.significant implementation of TQM with dimensions of focus on leadership, strategic planning, and customer focus towards competitive advantage with.mark.p-value.as big as.0.001 (H2 accepted). There is.influence.product quality has a significant impact on competitive advantage with.p-value of.0.041 (H3 accepted). From direct effect and induced testsIt is known that the direct effect of TQM on competitive advantage is 0.331 and the indirect effect of TQM implementation oncompetitive advantagethrough product quality (mediation variable) of 0.462, meaning the mediation was successful. Product quality is able to mediate between TQM implementation and competitive advantage.